Art as a Way of Knowledge - Cantelo, Brenda (Ethnologies, 2003)
Abstract“Art as a way of knowledge” examines ways in which themes of spiritual development and ultimate transformation can be expressed through movement. The discussion follows the artist through the phases of creation of a dance video, Animus, and offers a Jungian interpretation of the piece. Animus looks at one woman’s journey of spiritual transformation. It shows a central female character (the anima), moving in and out of relationship with three male characters, two human and one animal, who represent her masculine side, or animus. Moving through a dreamscape of her own unconscious, she begins to interact more consciously with her masculine side and eventually comes to terms with it. Ultimately, she overcomes fragmentation and integrates male and female, spirit and body in the composite symbol of the Self at the end.